Establishing a novel adaptive fuzzy control algorithm for an active stabilizer bar with complex automotive dynamics model - Tuan Anh Nguyen (Ain Shams Engineering Journal, 2024)
Rollovers can cause many hazards to the passengers in the car. The main cause of this problem is the driver's sudden steering at high speed to avoid an obstacle or enter a roundabout. To limit this phenomenon, it is necessary to equip the car with an active stabilizer bar. In this article, we use a new fuzzy control method to direct an active stabilizer bar. This method is established based on five points of view regarding the stability and responsiveness of the system, so it is called the novel adaptive fuzzy algorithm (NAFC). This is a completely new point in the article compared to previous studies. A combined dynamics model that is a fusion of the seven DOFs spatial dynamics model and the three DOFs motion model. The simulation and calculation occur in the Simulink® interface, with two cases representing the steering angles J-turn and Fish-hook. The speed of the car is changed according to three specific values. According to the calculation results, the vehicle body roll angle is greatly reduced when using active stabilizer bars controlled by the novel adaptive fuzzy algorithm. Besides, the minimum dynamic force value at the rear wheel is better guaranteed. The car's roll index is also sharply reduced when applying this algorithm to the hydraulic stabilizer bar model. In addition, rollover occurs when the car steers the J-turn at v3 and the fish hook at v2 and v3 (if stabilizer bars are unavailable). Meanwhile, car’s stability is always guaranteed in the case of a car with a stabilizer bar using the NAFC algorithm. The article's achievements can be used as a basis for developing more complex control algorithms in the future.